DAMPAK PENETAPAN HARGA TERHADAP PROFITABILITAS PADA BISNIS KEMITRAAN KULINER AYAM GORENG PT EVALINDA BERKAH MANDIRI JAKARTA SELATAN - Awalunnisa; Lily Setyawati Kristianti (Journal of Research and Publication Innovation, 2024)
This study aims to determine the impact of pricing on profitability in the culinary partnership business of fried chicken PT Evalinda Berkah Mandiri South Jakarta. The sampling technique used the Non-Probability Sampling technique, namely Saturated Sampling. Data processing in this study used the SPSS (Statistical Package for Social Science) software program version 27.0. The research method uses a quantitative method research type with a descriptive approach. While the analysis technique uses classical assumption test analysis (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test), simple linear regression test, correlation coefficient test, determination coefficient test and hypothesis test (t test). The results of the study showed that there was no impact of pricing on profitability in the culinary partnership business of fried chicken PT Evalinda Berkah Mandiri South Jakarta. Based on the results of the hypothesis test (t-test) the pricing variable on profitability showed that the calculated t value <t table and significant> 0.05, namely; 1.228 <2.080 and significant 0.233> 0.05. Based on the results of the determination coefficient test, the R square value is 0.067 or 6.7%. This means that the Pricing variable (X1) on Company Profitability (Y) is 6.7% while the remaining 93.3% is influenced by the variable. Judging from the results of the correlation coefficient test, the R value is 0.259. This shows that the correlation between pricing and profitability is considered